Realizing Apology Speech Acts in EFL: A Case Study of English Department Students at Universitas Negeri Semarang - Irhami, Moh. Akhdan Aufarizal; Yuliasri, Issy (Universitas Negeri Semarang, 2025)
This study aimed to find out how English Department students at Universitas Negeri Semarang realize the speech act of apology in English and how certain social variables influence their realization. The study is grounded in Olshtain and Cohen’s (1983) taxonomy of apology strategies and Brown and Levinson’s (1987) politeness theory, which addresses the roles of power, social distance, and rank of imposition. Using a qualitative case study design, this study employed a written Discourse Completion Task (DCT) with ten situations involving differences in power, social distance, and offense severity. The subjects of this study were 20 students from the second semester. The collected data were analyzed using a categorization framework based on the five apology strategies by Olshtain and Cohen and contextual factors by Brown and Levinson. The findings showed that explicit expression of apology was the most frequently used strategy and promise for forbearance was the least frequently used strategy. Students were more likely to combine several strategies in their realization of apology speech act rather than using a single strategy. It also revealed that students adjust their apologies according to context, demonstrating awareness of social roles and communication appropriateness. The study concluded that the students can realize their apology speech act based on contextual factors such as power, social distance, and offense severity by their appropriateness in selecting and combining the strategies.